FDI and economic growth: New evidence on the role of financial markets - Azman-Saini, W.N.W.; Law, Siong Hook; Ahmad, Abd Halim @ Hamilton (Elsevier, 2010)
This study uses a threshold regression model and finds new evidence that the positive impact of FDI on growth "kicks in" only after financial market development exceeds a threshold level.Until then, the benefit of FDI is non-existent.